SHP1-ing thymic selection - Gascoigne, N; Brzostek, J; Mehta, M; Acuto, O (John Wiley and Sons, Inc, 2016)
Thymocyte development and maintenance of peripheral T-cell numbers and functions are critically dependent on T-cell receptor (TCR) signal strength. SHP1 (Src homology region 2 domain-containing phosphatase-1), a tyrosine phosphatase, acts as a negative regulator of TCR signal strength. Moreover, germline SHP1 knockout mice have shown impaired thymic development. However, this has been recently questioned by an analysis of SHP1 conditional knockout mice, which reported normal thymic development of SHP1 deficient thymocytes. Using this SHP1 conditional knockout mice, in this issue of the European Journal of Immunology, Martinez et al. [Eur. J. Immunol. 2016. 46: 2103-2110] show that SHP1 indeed does have a role in the negative regulation of TCR signal strength in positively selected thymocytes, and in the final maturation of single positive thymocytes. They report that thymocyte development in such mice shows loss of mature, post-selection cells. This is due to increased TCR signal transduction in thymocytes immediately post positive-selection, and increased cell death in response to weak TCR ligands. Thus, SHP1-deficiency shows strong similarities to deficiency in the T-cell specific SHP1-associated protein Themis.